Optimal load shedding based on frequency, voltage sensitivities and AHP algorithm - Bùi Quang Anh; Quyền Huy Ánh; Lê Trọng Nghĩa (Journal of Technical Education Science, 2013)
Voltage and frequency are the two important parameters affecting the maintenance of the power system stability. This paper presents the load shedding methodology based on frequency and voltage. The level of disturbance is estimated by using the rate of frequency change, and determine the location, number of loads shed at each bus is determined based on the calculated voltage sensitivity at each bus in steady state. In the competitive electricity market, load shedding/not shedding Decision Support Systems are needed to find economical ways to serve critical loads with limited sources under various uncertainties. Decision - making is significantly affected by limited energy sources, generation cost, and network available transfer capacity. The load shedding program taking into account the importance and position of the load, investment rates per unit load, and the constraint conditions based on Analytic Hierarchy Process (AHP) algorithm to process when the system there are many different types of load.